PENGARUH SM ENTERTAINMENT DALAM PERKEMBANGAN DIPLOMASI BUDAYA KOREA SELATAN - Mutiara Megantari Putri (Journal of International Relations, 2022)
The Korean Wave is a pop culture from South Korea that has become a phenomenon spreading widely throughout the world. The Korean Wave consist of music, movie, drama, fashion, and lifestyle. The spread of Korean Wave started from a high demand of chinese community towards South Korean pop culture until it spread to all corners of Asia and the rest of the world. Because of high demand the Korean Wave, it had also saved South Korea from economic crisis in 1997 which made the government started using pop culture as a main tool to strengthen the country. SM Entertainment is one of the entertainment companies that participates in the spread of the Korean Wave through music, has a great contribution to current growth of the Korean Wave. The success of SM Entertainment also made SM Entertainment become a perfect actor for to spread South Korea influence. This research discusses how South Korea uses cultural diplomacy by using SM Entertainment as an actor of cultural diplomacy to exercise its soft power in achieving its goals. This research uses the concept of soft power and cultural diplomacy in analyzing SM Entertainment and South Korea by collecting qualitative data from analysis of journals, books, websites, and documentation of Korean Wave phenomenon and SM Entertainment activities. The results of this research indicate that SM Entertainment take a huge part of South Korea cultural diplomacy to other countries. Keywords: SM Entertainment, South Korea, Cultural Diplomacy, Soft Power, Korean Wave